The Use of Lumbricus Rubellus Earthworm Effect in Composting Process of Musa Paradisiaca L. Peel Waste - Vely Kukinul Siswanto; Vivin Setiani; Ayu Nindyapuspa; Ummi Fadlilah Kurniawati; Mutiara Mayang Kamilah (Universitas Diponegoro, 2021)
Conventional organic waste composting is one of the processing of organic waste that produces fertilizer. However, the conventional composting process for organic waste lasts 1-3 months. Vermicomposting is composting that lasts a short time, and in addition, vermicomposting produces compost and worms with a high selling value. So, in this study, Musa Paradisiaca L (MPL) peel and sawdust waste were composted using the vermicomposting method into compost. The primary data in this study consisted of monitoring the C/N ratio, temperature, pH, moisture content, texture, the particle size of compost for 3 weeks of the composting process. Testing the analysis of the effect of using Lumbricus Rubellus (LR) earthworms in the composting process of MPL peel waste and sawdust by using LR earthworms. The study results showed that LR worms had no effect on temperature, pH, water content, and C/N ratio during the composting process of MPL peel waste but did affect the texture, particle size, and product of compost weight. pH, moisture content, and temperature of compos with adding LR earthworms and without LR worms was 7, less than 50%, 27-29 0C, respectively. The C/N ratio of compost that uses LR earthworms was 28, while the C/N ratio of composting that uses LR earthworms was 33.